Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
Please check the explanation.
Step-by-step explanation:
Given the sequence
11, 13, 15, 17, 19, ...
Determining the Recursive formula:
We know that a recursive formula is termed as a formula that specifies each term of the given sequence using the preceding terms.
From the given sequence it is clear that every term can be obtained by adding two to the previous term.
i.e. 13 = 11+2, 15 = 13+2, 17 = 15+2, 19 = 17+2
so
aₙ₊₁ = aₙ+2, for n ≥1
Therefore, a recursive formula is:
- aₙ₊₁ = aₙ+2, for n ≥1
Determining the Explicit formula:
Given the sequence
11, 13, 15, 17, 19, ...
An arithmetic sequence has a constant difference 'd' and is defined by
[tex]a_n=a_1+\left(n-1\right)d[/tex]
computing the differences of all the adjacent terms
[tex]3-11=2,\:\quad \:15-13=2,\:\quad \:17-15=2,\:\quad \:19-17=2[/tex]
The difference between all the adjacent terms is the same and equal to
[tex]d=2[/tex]
also
[tex]a_1=11[/tex]
so substituting [tex]d=2[/tex], [tex]a_1=11[/tex] in the nth terms
[tex]a_n=a_1+\left(n-1\right)d[/tex]
[tex]a_n=2\left(n-1\right)+11[/tex]
[tex]a_n=2n+9[/tex]
Therefore, the Explicit formula is:
[tex]a_n=2n+9[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.